Using transcriptomics to inform the next generation risk assessment of doxorubicin and niacinamide - Tulum, Elizabeth Ann (2024)
Human health risk assessments without generating new animal data have resulted in extreme efforts over the past few decades from industry, academia, and regulatory bodies to develop and apply new method approaches. Various non-animal approaches for chemical hazard characterisation has appeared known as new approach methodologies (NAMs) which form the basis of integrated testing and assessment strategies designed to prevent harm to human health.